2019
DOI: 10.7554/elife.40765
|View full text |Cite
|
Sign up to set email alerts
|

Decreased brain connectivity in smoking contrasts with increased connectivity in drinking

Abstract: In a group of 831 participants from the general population in the Human Connectome Project, smokers exhibited low overall functional connectivity, and more specifically of the lateral orbitofrontal cortex which is associated with non-reward mechanisms, the adjacent inferior frontal gyrus, and the precuneus. Participants who drank a high amount had overall increases in resting state functional connectivity, and specific increases in reward-related systems including the medial orbitofrontal cortex and the cingul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 69 publications
4
55
0
Order By: Relevance
“…Similarly, individuals with alcohol use disorder, (Chanraud, Pitel, Pfefferbaum, & Sullivan, 2011) reported desynchronized low frequency rs-fMRI signals from the PCC and cerebellum. Nicotine (a key ingredient of tobacco) was also associated with decreased activity in the regions of DMN (Tanabe et al, 2011) and low overall functional connectivity (Cheng et al, 2019). From the vast pool of scientific studies, it can be inferred that tobacco and drugs intake, along with marijuana and alcohol use are associated with differences in rs time courses (Cheng et al, 2014), and are possibly making adolescents more vulnerable to psychiatric and other disorders (Thijssen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, individuals with alcohol use disorder, (Chanraud, Pitel, Pfefferbaum, & Sullivan, 2011) reported desynchronized low frequency rs-fMRI signals from the PCC and cerebellum. Nicotine (a key ingredient of tobacco) was also associated with decreased activity in the regions of DMN (Tanabe et al, 2011) and low overall functional connectivity (Cheng et al, 2019). From the vast pool of scientific studies, it can be inferred that tobacco and drugs intake, along with marijuana and alcohol use are associated with differences in rs time courses (Cheng et al, 2014), and are possibly making adolescents more vulnerable to psychiatric and other disorders (Thijssen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine (a key ingredient of tobacco) was also associated with decreased activity in the regions of DMN (Tanabe et al, 2011) and low overall functional connectivity (Cheng et al, 2019). From the vast pool of scientific studies, it can be inferred that tobacco and drugs intake, along with marijuana and alcohol use are associated with differences in resting state time courses (Cheng et al, 2014), and are possibly making adolescents more vulnerable to psychiatric and other disorders (Thijssen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…4 The medial OFC mediates internal control of mood and neurovegetative functions 3 (symptoms such as weight change, insomnia and fatigue) and seems to be mediate reward. 8 The lateral OFC seems to mediate empathic and socially appropriate behaviour; integrates the relationship between an external object and affect (emotional response), and responds to numerous punishing and unpleasant stimuli (such as bad smells and losing money) as well as to not receiving an expected reward. 3,4 Brain scans, for example, show activation of the human lateral OFC when the subject does not obtain an expected reward.…”
Section: Two Divisionsmentioning
confidence: 99%
“…The study found that smokers and drinkers had contrasting patterns of cortical functional connectivity involving the OFC. 8…”
mentioning
confidence: 99%